UNDERSTANDING YOUTH MENTAL HEALTH: A NARRATIVE REVIEW - Faida Annisa (Nurse and Health, 2025)
Youth mental health has increasingly become a global health concern. Depression in Indonesia has the highest rate of this age group compared to all age groups. Age 15-24 years is a key phase of identity formation, emotional growth, and social transition; therefore, mental health difficulties during this time can have lifetime effects. This review draws on recent literature to explore global patterns in youth mental health, to gain understanding into youth's perceptions, and a variety of social and digital influences as key barriers to early recognition and effective coping. The paper underscores the importance of promotive and preventive strategies, including mental health education, coping skills training, and early intervention programs. Emphasis is placed on culturally responsive and developmentally appropriate approaches that meet youth where they are—emotionally, socially, and digitally. Recommendations are offered for nursing and community practice, with a focus on building youth resilience and improving access to timely, stigma-free support systems.